2014
DOI: 10.1063/1.4868556
|View full text |Cite
|
Sign up to set email alerts
|

Liquid 1-propanol studied by neutron scattering, near-infrared, and dielectric spectroscopy

Abstract: Liquid monohydroxy alcohols exhibit unusual dynamics related to their hydrogen bonding induced structures. The connection between structure and dynamics is studied for liquid 1-propanol using quasi-elastic neutron scattering, combining time-of-flight and neutron spin-echo techniques, with a focus on the dynamics at length scales corresponding to the main peak and the pre-peak of the structure factor. At the main peak, the structural relaxation times are probed. These correspond well to mechanical relaxation ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
81
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(94 citation statements)
references
References 101 publications
(129 reference statements)
11
81
0
Order By: Relevance
“…This spectral feature is interpreted to originate from the same supramolecular structures responsible for the dielectric Debye process, and is identical to what is observed for short chain polymers. 21,22 Furthermore, it has been shown that also nuclear magnetic resonance, 17 dynamic light scattering, 3 and quasi-elastic neutron scattering 23 are sensitive to the Debye-process and similar results have been seen in mechanical studies of supramolecular polymers 1 and high temperature alcohols.…”
supporting
confidence: 57%
“…This spectral feature is interpreted to originate from the same supramolecular structures responsible for the dielectric Debye process, and is identical to what is observed for short chain polymers. 21,22 Furthermore, it has been shown that also nuclear magnetic resonance, 17 dynamic light scattering, 3 and quasi-elastic neutron scattering 23 are sensitive to the Debye-process and similar results have been seen in mechanical studies of supramolecular polymers 1 and high temperature alcohols.…”
supporting
confidence: 57%
“…1 shows broadband loss spectra of 1-propanol obtained by conventional low-field dielectric spectroscopy, measured at various temperatures. As demonstrated in [26], where part of these data were already shown, these spectra can be reasonably fitted by the sum of three peak functions. For the curve at 112 K, these peak at the low well descr relaxation which a Co 1-propanol found in c was accou relaxation [20,21,31] the secon monohydro of dynamic are assume [32] but, microscopi dependent relaxation fits, are c discussed significant…”
Section: Methodsmentioning
confidence: 84%
“…It was shown [46], that the excess wing is caused by a secondary relaxation peak that is partly submerged under the dominating  peak. The  relaxation in 1-propanol can be assumed to be of Johari-Goldstein type [20,21,26,31]. The same was suggested for the secondary relaxation causing the excess wing in canonical dipolar glass formers like glycerol [46,47] (but also other opinions exist; see, e.g., [48]).…”
Section: -Relaxationmentioning
confidence: 97%
See 1 more Smart Citation
“…12(a)) and peak in " (Fig. 12(b)) while the  and  relaxations in this alcohol only show up as weak shoulders [127]. The insets of Fig.…”
Section: Monohydroxy Alcoholsmentioning
confidence: 99%